2010
DOI: 10.1007/s11745-010-3407-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics and Partitioning of Di‐tert‐butyl Nitroxide in Stratum Corneum Membranes: Effect of Terpenes

Abstract: In this work, we have used electron paramagnetic resonance (EPR) spectroscopy of the small spin label di-tert-butyl nitroxide (DTBN), which partitions the aqueous and hydrocarbon phases, to study the interaction of the terpenes alpha-terpineol, 1,8-cineole, L(-)-carvone and (+)-limonene with the uppermost skin layer, the stratum corneum, and the membrane models of 1,2-dipalmitoyl-sn-glycero-3-phosphatidylcholine (DPPC) and 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC). The EPR spectra indicated that the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Anjos and co-workers (29) have shown, using EPR with 5-DS, that 1,8-cineole, a main constituent of Vac, modifies the properties of cell membranes by rupturing the hydrogen-bonded network at the membrane-water interface, but not by changing membrane fluidity near the surface. Similar results were obtained for limonene and other related compounds (30). The ability to increase the susceptibility of the membrane to the penetration of various compounds seems to be a general characteristic of cyclic terpens (31).…”
Section: Discussionsupporting
confidence: 79%
“…Anjos and co-workers (29) have shown, using EPR with 5-DS, that 1,8-cineole, a main constituent of Vac, modifies the properties of cell membranes by rupturing the hydrogen-bonded network at the membrane-water interface, but not by changing membrane fluidity near the surface. Similar results were obtained for limonene and other related compounds (30). The ability to increase the susceptibility of the membrane to the penetration of various compounds seems to be a general characteristic of cyclic terpens (31).…”
Section: Discussionsupporting
confidence: 79%
“…Terpenes in combination with ethanol also increased the permeability of luteinizing hormone releasing hormone through porcine skin by enhancing the extraction of stratum corneum lipids [28]. It has been shown that the membrane partition coefficients of the small watersoluble spin labels TEMPO and DTBN in the stratum corneum and in DPPC membranes increase with increasing temperature, with the greatest increases for temperatures above the phase transition of the membranes [14,15]. In this work, the EPR signal of 5-DMS in terpene micelles present in the system of DPPC vesicles:terpenes was generally observed for temperatures below 30°C, suggesting that with increasing temperature more terpenes penetrate in DPPC bilayers, forming a minor amount of micelles.…”
Section: Discussionmentioning
confidence: 99%
“…The electron paramagnetic resonance (EPR) spectroscopy of spin labels has been employed to investigate the mechanisms by which monoterpenes act as enhancers of skin permeation [12][13][14][15]. The intercellular lipid matrix of the outermost skin layer, the stratum corneum, which is the major permeability barrier of the skin, becomes more fluid in the presence of the monoterpenes L-menthol and 1,8-cineole [12,13], and several monoterpenes increase the membrane partition coefficients of the small water-soluble spin labels TEMPO and DTBN in stratum corneum membranes [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron paramagnetic resonance (EPR) spectroscopy using spin labels has been employed to investigate the mechanisms underlying the acceleration of skin permeation by monoterpenes [20][23]. The intercellular lipid matrix of the stratum corneum, the outermost skin layer, which represents the major permeability barrier of the skin, becomes more fluid in the presence of the monoterpenes L-menthol and 1,8-cineole [20], [21].…”
Section: Introductionmentioning
confidence: 99%